ESTUDO DOS SISTEMAS CeO2(1-x) :Pr6O11(x); CeO2(1-x):Fe2O3(x) E CeO2(0,95-x): Pr6O11(0,05):Fe2O3(x) PARA APLICAÇÃO COMO PIGMENTOS INORGÂNICOS DE BAIXA TOXICIDADE - Olegario, Renata Cristina (2012)
This study focused on the Cerium oxide (CeO2) based pigmenting systems, doped with Praseodymium oxide (Pr6O11) and hematite (Fe2O3 – iron oxide) synthesized through the solid state reaction (OM – oxide mixture) and the Pechini method. Simultaneously, CeO2-Pr6O11-Fe2O3 ternary system pigments were synthesized through OM, with the addition of mineralizers. The samples synthesized through OM were wet homogeneized, in isopropyl alcohol, in a horizontal ball mill for 18 hours and dried in oven at 110 C, then thermally treated at 1300 ºC for 3 hours. In samples synthesized through the Pechini method, the process started from the synthesis of the polymeric resin, formed by the citric acid reaction, glycol ethyl, water and the desired oxide salts, kept in thermal blanket at 150 C, under constant agitation for 2 hours, following two thermal treatments at 300 C for 2 hours, and then one at 900 C for 3 hours. After the thermal treatment the pigmenting systems were characterized through XRD, UV-Vis reflectance spectroscopy, scanning electronic microscopy, Raman spectroscopy and thermal analysis, determining the phases present, the colorimetric parameters, band gap values, micro-structural agglomerations and thermal and chemical stability to glass enamel. Single phase pigments were obtained in the binary system CeO2-Pr6O11, with addition of up to 10% Pr6O11 synthesized through OM and up to 3% Pr6O11 synthesized through the Pechini method, whereas the binary system CeO2-Fe2O3, presented single phase only in OM synthesis, with concentrations up to 2% of Fe2O3. More intense shades were obtained in pigments with addition of up to 5% mol praseodymium oxide in the CeO2-Pr6O11 system, and with up to 3% mol iron oxide in the CeO2-Fe2O3 system. The ternary system CeO2-Pr6O11-Fe2O3 presented secondary phase PrFeo3, remaining this phase even with the addition of mineralizers. The pigments applied to low temperature frits (LTF) and windscreen glass (WSG) showed chemically and thermally resistant at 800 C, free of surface defects on the ceramic plates, presenting better dispersion and color homogeneity.